Micropropagation of Dillenia philippinensis Rolfe - Lumeran, Belen T. (MSU Research Journal: official publication of the Research and Development Center Mindanao State University, General Santos City, 2002)
Culture of the mature seeds, shoot tips, nodes and leaves for callus and shoot formation is conducted for micropagation of Dillena philippinensis Rolfe using Knudson C and MS media with varying levels of BA and NAA. The following treatments are used: T0 (0 mg/L BA + 0 mg/L NAA), T1 (0.5 mg/L BA + 0.5 mg/L NAA), T2 (1.0 mg/L BA +1.0 mg/L NAA), T3 (2.0 mg/L BA + 2.0 mg/L NAA). Establishment of root calli, shoot tips and nodes from cultured seedlings is done on MS medium with different concentrations of BA and NAA (0, 0.5, 1.0 and 2.0 mg/L). Only the root calli develops shoots within 140-203 days from inoculation. Significant differences are found on the number of shoots, leaves and shoot height (in mm) of cultured seedlings, shoot tips and nodes established from full-grown seedlings using Kruskal-Wallis Test. Knudson C medium with a lower concentration of BA and NAA (0.5 mg/L) favors the formation of taller shoots with more leaves for the inoculated seeds while MS medium with the same concentration of BA and NAA (0.5 mg/L) induces taller shoots for the cultured shoot tips. Rooted microcuttings on semi-solid MS medium with 0.186 mg/L NAA alone are grown under greenhouse condition and are transferred later to the field. One hundred percent of the plantlets survived under greenhouse and field conditions. Results of this study show that even in vitro culture, the seeds can not be germinated easily which observations is due to its hard coat and thick helium. It is therefore, necessary to propagate this plant by tissue culture. This investigation also provides basic information on the propagation of D. philippinensis through tissue culture.